A note on the representative adaptive learning algorithm - Michele Berardi; Jaqueson K. Galimberti (ETH Zurich, KOF Swiss Economic Institute, 2014)
We compare forecasts from different adaptive learning algorithms and calibrations applied to US real-time data on inflation and growth. We find that the Least Squares with constant gains adjusted to match (past) survey forecasts provides the best overall performance both in terms of forecasting accuracy and in matching (future) survey forecasts.
Keywords: C53; D83; D84; E03; E37; 330; expectations; learning algorithms; forecasting; learning-to-forecast; least squares; stochastic gradient